Complete the Law on Contracts for Sale and Purchase of Goods in accordance with Vietnamese Law - Truc Linh, Huynh Thi; Gioi, Phan Minh (Jurnal Cita Hukum, 2025)
This study explores the role of economic law in promoting Vietnam’s economic growth and global integration, particularly focusing on the legal framework governing international contracts for the sale of goods. Using a qualitative research method with a normative-juridical and comparative approach, the study analyzes legal documents, case studies, and expert opinions to identify weaknesses in Vietnam’s current economic law system. Through in-depth interviews with legal scholars, business practitioners, and policymakers, as well as content analysis of international trade agreements, the research examines how inconsistencies in legislation and differences in legal interpretation often lead to contractual disputes and economic inefficiencies. The findings reveal that improving Vietnam’s economic law requires not only legislative reform to ensure consistency, transparency, and conformity with international legal standards, but also enhanced legal literacy among enterprises. By understanding and applying the law correctly, businesses can better safeguard their rights and optimize their participation in international trade. The research highlights the need for comprehensive legal education, institutional support, and harmonization efforts to strengthen Vietnam’s commercial legal infrastructure. Ultimately, the study concludes that aligning Vietnam’s economic law with international norms will promote more effective and sustainable global economic integration, boost investor confidence, and contribute significantly to the nation’s long-term economic resilience and competitiveness in the global market.